Optimal Strategies in Sports Economics and Management - Butenko, Sergiy; Gil-Lafuente, Jaime; Pardalos, Panos M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This volume presents original contributions from renowned researchers in sports economics, management, and optimization.The book discusses up-to-date developments in several topics, including resource allocation strategies in sports industry, impact of the financial crisis on professional sports around the world, fairness in sports competitions, and optimization-based gambling strategies. "Optimal Strategies in Sports Economics and Management" will be of interest not only to students, researchers and practitioners involved with the sports industry, but also to the general public interested in sports such as soccer, hockey, American football, basketball, golf, and jai alai.
Affinity in the Selection of a Player -- Game Systems in Team Sports -- The Impact of the Global Financial Crisis on Sport in North America -- Managing and Modeling the Combination of Resources in Professional Sporting Events -- Governance and Sporting Success of Top 20 Football Clubs After Economic Crisis -- The Stadium Game in an Uncertain Environment: A Preliminary Look at Arena Discourse in Edmonton, Canada -- A Complex Network Approach to Crisis Recovering in Sport Applications -- A Study of Fairness in Fourball Golf Competition -- Can Subsidies Help Buy Success? Revenue Sharing in English Football -- Commercial Football and the Economic Cycle -- Economics of Gambling on Sports: A Multistage Stochastic Programming Approach to American Jai Alai Gambling Strategies.
Keywords: Mathematics; Mathematical optimization; Finance; Mathematics; Financial Economics; Control; Calculus of Variations and Optimal Control; Optimization